PERAN RUTH BADER GINSBURG DALAM MENINGKATKAN KESETARAAN GENDER DI AMERIKA SERIKAT MELALUI WOMEN’S RIGHTS PROJECT DAN MAHKAMAH AGUNG AMERIKA SERIKAT - Miftahul Jannah; Yusnarida Eka Nizmi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study analyzes the role of Ruth Bader Ginsburg in escalate gender equality in America through her role in the Women’s Rights Project and the Supreme Court. This research is expected to be a guide in knowing  Ruth Bader Ginsburg's efforts in improving  gender equality in United States.             This study uses the principle of a feminist perspective where when discussing gender inequality, a feminist perspective is needed to analyze the interaction of Ruth Bader Ginsburg with the Women’s Rights Project and use feminism theory. The method used is a qualitative method that is collecting data through life history research of Ruth Bader Ginsburg             This research shows that Ruth Bader Ginsburg's role in advancing gender equality in America through the Women’s Rights Project has been well implemented from the cases she worked on starting from working on gender discrimination cases at the Women’s Rights Project, to cases of gender discrimination when she became a member of the Supreme Court Judge. Gender equality has become a part of her life which she strives for because she himself has felt gender inequality since she was young. With Ginsburg joining the Women’s Rights Project and becoming a Supreme Court Justice, Ginsburg has changed some of the perceptions and laws that state that gender discrimination hurts both men and women. Keywords: Ruth Bader Ginsburg, Women’s Right Project, Gender Equality, United States of America, Supreme Court Justice